Digital Marketing Strategy to Increase Sales in Warkop Gelas Batu 5 Ahmad Yani Rantauprapat - Rizki, Ade Indah; Elvina, Elvina; Halim, Abdul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
This research aims to find out how digital Warkop business marketing strategies via social media increase sales, the obstacles and challenges, and an economic review of Warkop marketing using social media. The location of this research is the Warkop Gelas Batu 5 Ahmad Yani Rantauprapat. The research method used is qualitative, using data collection techniques through observation, interviews, and documentation. From the results of this research, it can be concluded that to increase sales results, the businessman of Warkop Gelas Batu 5 Ahmad Yani Rantauprapat uses 10 social media marketing strategies for small-scale businesses using WhatsApp, Instagram, and Facebook, namely: social media marketing strategies by building credibility, attracting potential customers, build relationships on social media, share accurate content, create valuable content, use good and interesting images, crowdsource for interesting and authentic content, participate in online groups and communities, use social media as a space to hold interesting and limited conversations social media platforms.